Looking for Alaska - John Green (USA Penguin Group, 2013)
First drink, first prank, first friend, first girl, last words... A poignant and moving crossover novel about making friends and growing up from American author, John Green. Miles Halter is fascinated by famous last words - and tired of his safe, boring and rather lonely life at home. He leaves for boarding school filled with cautious optimism, to seek what the dying poet Francois Rabelais called the "Great Perhaps." Much awaits Miles at Culver Creek, including Alaska Young. Clever, funny, screwed-up, and dead sexy, Alaska will pull Miles into her labyrinth and catapult him into the Great Perhaps. Looking for Alaska brilliantly chronicles the indelible impact one life can have on another.
Keywords: Fiction; Young Adult; Romance